Developing Millennial Generation Skills Through a Technology-Based Agribusiness Training Program in Mekarsaluyu Village, Cimenyan District, West Java Regency - Muhammad, Achmad; Sadikin, Supriyadi; Sudjana, Dede; Syukri, Khariful; Attaqwa, Yusita (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2026)
This community service activity aims to increase the understanding, knowledge, and interest of the younger generation in Mekarsaluyu Village towards technology-based agribusiness. The method of implementing activities uses a socialization method that is carried out in a structured manner through the delivery of materials and interactive discussions. The target of the activity is students and youth of Mekarsaluyu Village who have not been actively involved in agricultural activities. The results of the activity showed an increase in participants' understanding and interest in the technology-based agriculture and agribusiness sectors. Through this activity, the young generation is expected to be able to play an active role in the sustainable development of village agricultural potential and encourage innovative and competitive agribusiness-based local economic growth.